Optimal SSSC-based power damping inter-area oscillations using firefly and harmony search algorithms - Naderipour A.; Abdul-Malek Z.; Ramachandaramurthy V.K.; Miveh M.R.; Moghaddam M.J.H.; Guerrero J.M. (Nature Research, 2023)
algorithm; article; data analysis software; firefly; nonhuman; oscillation; simulation